O trabalho dos pastores de igrejas pentecostais não denominacionais - Francisco Zucchelli Lott (2018)
The Pentecostalism was founded in the United States and spread all over the world, configuring a notable expansion into the third world. In Brazil this expansion occur in a continuous way through more than a century followed by a diminution of the catholic population. With the catholic decline follows a process of institutional decentralization of religion among the Protestants where it is remarkable the possibility of the foundation of new churches with great easiness. Besides that, the profit and the savings of money dont contradict the Pentecostal religions speech which is based on the Prosperity Theology. Taking as a beginning point the religion action as a rational action in which the experts of the mythical speech have a central role, we ask how is the social construction of the religiös musikalisch? Or in another way, what kind of work is the pastors work? This research shows how the routine of the pastors work is and discuss about their life history and their carrier. We show as well the incidence of formality and informality, their means of reward, the product of their work and the relation of the religious work with the secular work. To achieve that, our method was the observation with a composition of a field notebook in a nondenominational Pentecostal church in the circumscriptions of a suburb neighborhood located on the Belo Horizonte city. Also, we have made interviews of life story in which we give emphasis to life aspects of the subjects interviewed, focusing only the sufficient to make the themes of our interest in this research appear. We made four interviews with four pastors from two different churches. We conclude that the pastors work doesnt occur in a regulated relation and theres frequently observed a function deviation that is accepted by the pastors since its related with the church. Yet, we conclude that the product of the pastors work attach, in an inseparable way, the assistance to the low class population and the reproduction of a speech founded in the teleological conception of a dual view of the world that justifies the mitigation of the importance of the attribution of an ontology meaning to the material world.